Limberg Flap for Pilonidal Sinus - Muhammad Waqas Raza, Syed Fahad Ali Zaidi, Afzaal Amin Mughal, Haroon Rasheed, Aurangzeb Khan, Saleem Shahzad Gondal, Waseem Iqbal Sheikh (Journal of Rawalpindi Medical College, 2012)
Background: To evaluate Rhomboid excision and Limberg flap reconstruction for pilonidal sinus in terms of complications, hospitalization time, days to return to work and recurrence. Methods: Patients with simple, complex and recurrent pilonidal sinus were studied. Patients presenting with acute abscess were excluded. Patients were followed for a minimum period of one year to determine the recurrence of disease. Results: Over a period of four years 68 patients underwent classical Limberg flap for pilonidal sinus. A total of 11(19%) had complications including a major wound infection causing wound disruption and 3 (4.4%) recurrent cases were seen. Conclusions: Rhomboid excision and Limberg flap reconstruction for pilonidal sinus is a satisfactory method of achieving surgical cure of disease.